Clinical Trial and In Vitro Study for the Role of Cartilage and Synovia in Acute Articular Infection. (10th November 2015) - Langenmair, Elia R.; Kubosch, Eva J.; Salzmann, Gian M.; Beck, Samuel; Schmal, Hagen
Abstract : Objective . Osteoarthritis is a long-term complication of acute articular infections. However, the roles of cartilage and synovia in this process are not yet fully understood. Methods . Patients with acute joint infections were enrolled in a prospective clinical trial and the cytokine composition of effusions compared in patients with arthroplasty ( n = 8) or with intact joints ( n = 67). Cytokines and cell function were also analyzed using a human in vitro model of joint infection. Results . Synovial IL-1 β levels were significantly higher in patients with arthroplasty ( p = 0.004). Higher IL-1 β concentrations were also found in the in vitro model without chondrocytes ( p < 0.05). The anti-inflammatory cytokines IL-4 and IL-10 were consistently expressed in vivo and in vitro, showing no association with the presence of cartilage or chondrocytes. In contrast, FasL levels increased steadily in vitro, reaching higher levels without chondrocytes ( p < 0.05). Likewise, the viability of synovial fibroblasts (SFB) during infection was higher in the presence of chondrocytes. The cartilage-metabolism markers aggrecan and bFGF were at higher concentrations in intact joints, but also synthesized by SFB. Conclusions . Our data suggest an anti-inflammatory effect of cartilage associated with the SFBs' increased resistance to infections, which displayed the ability to effectively synthesize cartilage metabolites.The trial is registered with DRKS 00003536, MISSinG.